Beyond Economics: the Family, Belonging and Remittances among the Bangladeshi Migrants in Los Angeles. (16th January 2021) - Mahmud, Hasan
Abstract: This paper presents a study exploring how migrants' belonging shapes their remittances among Bangladeshi migrants in Los Angeles. Based on migrants' perception, the paper recognizes the centrality of the family and origin community in migrants' remittances both in the NELM and in the transnational perspectives. It empirically investigates migrants' belonging and recognizes their membership in their parents' family, their own nuclear family, joint family including siblings with their respective families, extended family including multiple generations and a community of origin. It finds migrants' belonging simultaneously to the destination and origin countries, and also confirms the presence of 'friction' in such belonging, indicative of both cooperation and conflict in migrants' remittances allowing for explaining changes in their remittances such as remittances decay and resurgence. This study offers guideline for further empirical research on migrants' transnationalism and remittances with policy implications regarding the developmental consequences of remittances.